Integrating ultra‐fast charging stations within the power grids of smart cities: a review. Issue 1 (19th April 2018) - Meyer, Danielle; Wang, Jiankang
Abstract : Plug‐in electric vehicles (PEVs) have become a key factor driving towards smart cities, which allow for higher energy efficiency and lower environmental impact across urban sectors. Industry vision for future PEV includes the ability to recharge a vehicle at a speed comparable to traditional gas refuelling, i.e. <3 min. per vehicle. Such a technology, referred to as ultra‐fast charging (UFC), has drawn much interest from research and industry. However, UFC poses unprecedented challenges to existing electricity supply infrastructure due to its large power density, impulsive, and stochastic load characteristics. Planning the locations and electric capacities of UFC stations is critical to preventing detrimental impacts. In particular, efforts must be made of mitigate grid asset depreciation, grid instabilities, and deteriorated power quality. The authors first review planning methods for conventional charging stations. Next, they discuss outlooks for UFC planning solutions by drawing an analogy with renewable energy (RE) source planning. This analogy is based on the similar power density and stochastic characteristics of RE and UFC. While this study mainly focuses on UFC planning from the power grid perspective, other urban aspects, including traffic flow and end‐user behaviour, are examined for feasible UFC integration within smart cities.